RATIO LEGIS PENGATURAN PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) MENGGANTIKAN KEBERADAAN PEGAWAI TIDAK TETAP DI LINGKUNGAN INSTANSI PEMERINTAH DALAM HUKUM KEPEGAWAIAN INDONESIA - Rajab Maliq, Ahdi; Lumban Gaol, Selamat (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
The existence of Law of the Republic of Indonesia Number 5 of 2014 concerning State Civil Apparatus is different from previous civil service laws. Therefore, it is very interesting and important to study further regarding what legal ratios regulate Government Employees with Work Agreements (PPPK) to replace the existence of non-permanent employees in the Indonesian civil service system in Law Number 20 of 2023 concerning State Civil Apparatus? and how to implement the protection of the rights, obligations and responsibilities of Government Employees with a Work Agreement (PPPK) within Government agencies within Indonesian civil service law. To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that when the law came into force on October 31 2023, Law Number 5 of 2014 concerning State Civil Apparatus was revoked and declared invalid. What's new is what you need to know about the provisions of Law Number 20 of 2023: a) The 2023 ASN Law provides the same rights for civil servants and PPPK; b) there are no longer the terms Central Civil Servants and Regional Civil Servants; c) Certain ASN positions can be filled by TNI soldiers and members of the Republic of Indonesia Police; d) ASN Employee Rights; e) ASN employees can be dismissed if they do not perform; f) Honorary honorary appointments are not permitted; and g) Non-ASN employees or other names must have their arrangements completed no later than December 2024 and from the time this Law comes into force. The facts on the ground are that there is still a lot of discriminatory treatment for PPPK ASN.